Colorectal cancer screening: a comparison of 35 initiatives in 17 countries. - Benson, V; Patnick, J; Davies, A; Nadel, MR; Smith, R; Atkin, W (2008)
Although in its infancy, organized screening for colorectal cancer (CRC) in the general population is increasing at regional and national levels. Documenting and describing these initiatives is critical to identifying, sharing and promoting best practice in the delivery of CRC screening. Subsequently, the International Colorectal Cancer Screening Network (ICRCSN) was established in 2003 to promote best practice in the delivery of organized screening programs. The initial aim was to identify and document organized screening initiatives that commenced before May 2004. Each identified initiative was sent 1 questionnaire per screening modality: fecal occult blood test, flexible sigmoidoscopy or total colonoscopy. Information was collected on screening methodology, testing details and initiative status. In total, 35 organized initiatives were identified in 17 countries, including 10 routine population-based screening programs, 9 pilots and 16 research projects. Fecal occult blood tests were the most frequently used screening modality, and total colonoscopy was seldom used as a primary screening test. The eligible age for screening ranged from 40 years old to no upper limit; most initiatives included participants aged 50 to 64. Recruitment was usually done by a mailed invitation or during a visit to a family physician. In conclusion, this is the first investigation describing the delivery of CRC screening protocols to various populations. The work of the ICRCSN is enabling valuable information to be shared and a common nomenclature to be established.